ANALISIS KESULITAN SISWA DALAM MEMECAHKAN SOAL SISTEM PERSAMAAN LINEAR DUA VARIABEL BERDASARKAN TAHAPAN POLYA PADA SISWA KELAS IX DI SMP KATOLIK GONZAGA TOMOHON - Brayen Harly Tilaar; Sylvia J. A. Sumarauw; Murni Sulistyaningsih (JURNAL LEMMA, 2026)
Difficulties in solving System of Linear Equations in Two Variables (SLETV) remain a persistent challenge for junior high school students. This study investigated where and why those difficulties occur by mapping students' performance against the four stages of Polya's heuristic framework. A qualitative design with a phenomenological approach was adopted to capture the lived experience of 24 ninth-grade students at SMP Katolik Gonzaga Tomohon (odd semester, 2025/2026). Written problem-solving tests, unstructured phenomenological interviews, and classroom observation were employed as data sources; findings were cross-validated through technique and source triangulation as well as member checking. Achievement scores for the four stages were: understanding the problem 63.9% (good), devising a plan 45.8% (sufficient), carrying out the plan 58.3% (sufficient), and looking back 12.5% (very difficult). Two bottlenecks stood out: constructing a correct mathematical model of SLETV and selecting an appropriate solution method at the planning stage, and the near-complete absence of answer verification at the looking-back stage. Phenomenological interviews further revealed that students' obstacles are not confined to cognitive gaps; affective responses such as confusion, self-doubt, and fear of error especially when translating word problems into algebraic form substantially hindered systematic mathematical reasoning.